Revisiting the role of cell death in cancer – promotion rather than inhibition - Wang Rui-An; Li Zu-Guo (Visualized Cancer Medicine)
Cell death and its relations with cancer are subjects of significant misunderstanding within the scientific community, giving rise to numerous paradoxes. The prevailing perspective posits that oncogene activation diminishes cell death, resulting in accumulation of cells and the genesis of cancer. This article elucidates the difference between the pathological morphology of “necrosis” and the cellular demise concept of “necrosis” in cell biology, the influence of autophagy on cellular longevity, and the fundamentals of tumor suppression. It underscores the observation from pathology and literature that “resistance to apoptosis” is not an inherent trait of cancer. Rather than impeding, individual cell death actually fosters the progression of cancer as a whole. In fact, virtually all carcinogenic factors can trigger cellular apoptosis instead of extending cellular longevity. Contrary to conventional wisdom, genes promoting apoptosis exhibit carcinogenic properties, while those inhibiting apoptosis and cellular protective elements demonstrate anti-cancer effects. In essence, non-physiological cell death serves as a catalyst for tumorigenesis.